The social well-being of older adults in Singapore - TAN, Micah (Institutional Knowledge at Singapore Management University, 2023)
The concept of social well-being has been of interest especially when studying older adult well-being given that problems of social isolation and loneliness are more prevalent and have greater consequences for older adults (Waite 2018). However, much is still to be understood about the social well-being of older adults with most research being conducted on social predictors of health, rather than on social well-being as a specific “component of health” (Waite 2018:100). As such, the current research brief provides a preliminary examination of social well-being among middle-aged and older adults in Singapore based on Keyes’ social well-being framework (Keyes 1998). Using the Singapore Life Panel® (SLP), a localized version of Keyes’ instrument to measure social well-being was fielded. The current research brief offers preliminary results based on this instrument, including descriptive statistics of responses to the survey, as well as associations with other key factors including mental well-being, the frequency of participation in social activities, and the availability of neighborhood amenities. In terms of the organization of this paper, we first provide some brief background on the concept of social well-being and the instrument that was used to measure social well-being and fielded to the SLP. Subsequently, the findings will be presented in three main parts; the first presents descriptive frequencies of responses to the questions, as well as demographic distributions of responses. The second part presents correlations between several key social factors and social well-being, including the participation in social activities and the availability of neighborhood amenities. The final, third part examines how social well-being is correlated to mental well-being among middle-aged and older adults in Singapore. The brief then concludes with a short discussion of several implications of our findings.